2018
DOI: 10.1371/journal.pone.0189218
|View full text |Cite
|
Sign up to set email alerts
|

Exploring chronic disease in Bolivia: A cross-sectional study in La Paz

Abstract: PurposeThis study seeks to develop an understanding that can guide development of programs to improve health and care for individuals with Non-Communicable Diseases (NCDs) in La Paz, Bolivia, where NCDs are prevalent and primary care systems are weak. This exploratory investigation examines the characteristics of chronic disease patients in the region, key health related behaviors, and their perceptions of the care that they receive. The longer-term goal is to lay groundwork for interventional studies based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Bolivia is a LMIC with a human development index of 0.70 in 2018, ranked as 15th of the 20 countries in Latin-America [ 32 ]. It is characterised by a high prevalence of chronic disease and a weak PHC system [ 33 ] with a long history of selective programs and a biomedical hospital centric focus [ 34 ]. Notwithstanding the introduction in 2008 [ 35 ] of a public health care model based on intercultural community family health, encouraging broad participation while incorporating both Western and indigenous (traditional) medicines, progress has not been evaluated [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bolivia is a LMIC with a human development index of 0.70 in 2018, ranked as 15th of the 20 countries in Latin-America [ 32 ]. It is characterised by a high prevalence of chronic disease and a weak PHC system [ 33 ] with a long history of selective programs and a biomedical hospital centric focus [ 34 ]. Notwithstanding the introduction in 2008 [ 35 ] of a public health care model based on intercultural community family health, encouraging broad participation while incorporating both Western and indigenous (traditional) medicines, progress has not been evaluated [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the planning units of the Departmental Health Services and municipal governments do not have estimates of the magnitude of the problem locally, and therefore no prioritized interventions based on their own population characteristics can be properly implemented [9–11]. The existing studies in Bolivia have reported a high prevalence of obesity (60.7%) [12], high blood pressure (36%) [13], alcohol consumption (85%) [14], and sedentarism (67.2%) [15]. Nevertheless, these studies were focused on a limited number of risk factors, several were hospital-based, and none of them used the World Health Organization (WHO) STEPS methodology (Surveillance of Noncommunicable Diseases), so that they lacked a comprehensive picture of current cardiovascular and behavioural risk factors at the population level.…”
Section: Introductionmentioning
confidence: 99%
“…Bolivia is a LMIC with a human development index of 0.70 in 2018, ranked as 15 th of the 20 countries in Latin-America [32]. It is characterised by a high prevalence of chronic disease and a weak PHC system [33] with a long history of selective programs and a biomedical hospital centric focus [34]. Notwithstanding the introduction in 2008 [35] of a public health care model based on intercultural community family health, encouraging broad participation while incorporating both Western and indigenous (traditional) medicines, progress has not been evaluated [36,37].…”
Section: Introductionmentioning
confidence: 99%